Tailoring of Magnesium Substitution on Structure and Magnetic Properties of Lithium Ferrites - Mazurenko, Julia (Physics and Chemistry of Solid State, 2021)
In this study is reported influence of Mg2+ doping on structure and magnetic properties of nano-sized Li0.5Fe2.5-XMgXO4 (0.0, 0.2, 0.4, 0.6, 0.8) synthesized using sol-gel auto-combustion method. The X-ray diffractometric and Mössbauer data analysis of samples confirmed the formation of pure Li0.5Fe2.5-XMgXO4 nanoparticles ranges crystallite size from 15 nm to 35 nm. Iron ions are redistributed on the A and B sites in a ratio of approximately 4:6, and magnesium ions 8:2, respectively. The advantages of the B position of the above ions are as follows: Li+>Fe3+>Mg2+. RT-Mössbauer indicated the presence of 57Fe in both sublattices. Position identification was performed based on the distribution of the over exchange fields and isomeric shift data. Magnetic characteristics were obtained for rings made of synthesized material. They showed a non-monotonic dependence on the composition and found significantly higher rates compared to similar materials obtained by solid-phase synthesis.